2021
DOI: 10.1159/000518383
|View full text |Cite
|
Sign up to set email alerts
|

N-Cadherin Regulates GluA1-Mediated Depressive-Like Behavior in Adolescent Female Rat Offspring following Prenatal Stress

Abstract: <b><i>Background:</i></b> The incidence of depression is twice higher in women than in men, and gender differences in the prevalence rates first emerge around puberty. Prenatal stress (PS) induces gender-dependent depressive-like behavior in adolescent offspring, but the neuro-physiological mechanisms remain unclear. Our study aimed to investigate the possible neuro-physiological mechanisms of gender-dependent depressive-like behavior in PS adolescent offspring and further explored the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…59,60 Conversely, increased SYN 1 and PSD 95 expression can improve depression. 61,62 Consistent with our findings, GRd greatly reversed the significant decrease in SYN 1 and PSD 95 protein levels in the hippocampus of CUMS rats. This shows that the antidepressant-like effect of GRd is linked to the expression of hippocampal synaptic plasticity-related regulators.…”
Section: Discussionsupporting
confidence: 90%
“…59,60 Conversely, increased SYN 1 and PSD 95 expression can improve depression. 61,62 Consistent with our findings, GRd greatly reversed the significant decrease in SYN 1 and PSD 95 protein levels in the hippocampus of CUMS rats. This shows that the antidepressant-like effect of GRd is linked to the expression of hippocampal synaptic plasticity-related regulators.…”
Section: Discussionsupporting
confidence: 90%
“…GluA1 is critical for LTP and is associated with several neurological diseases (Ge & Wang, 2021; Gugustea & Jia, 2021). Based on genome‐wide association studies (GWAS), GluA1 dysfunction has been identified as a risk factor for schizophrenia (Ripke et al., 2014), while molecular and pharmacological studies in the last decade have identified GluA1 in depression, anxiety, stress‐related behavior and Alzheimer's disease (Minano‐Molina et al., 2011; Shao et al., 2021). Interestingly, GluA1 expression and phosphorylation levels appear to be important for these neurological conditions (An et al., 2021; Leal et al., 2020; Minano‐Molina et al., 2011; Roman‐Albasini et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In GluA1-deficient mice, hippocampal LTP was absent without spatial reference memory deficits [67], but working memory deficits [68], schizophrenia-like behaviors [69,70] and increased locomotor activity, accompanied by reduced clearance of striatal dopamine, was displayed [69]. While GWAS identified GluA1 dysfunction as a risk factor for schizophrenia [12], molecular and pharmacological studies over the past decade have linked GluA1 to depression, anxiety, stress-related behavior, and Alzheimer's disease [71][72][73][74]. Interestingly, the levels of GluA1 expression and phosphorylation appear to be important for these neurological conditions [71,73,75,76].…”
Section: Figurementioning
confidence: 99%